Characterization of polymorphic microsatellite DNA markers in the black-tailed godwit (Limosa limosa:Aves) - Verkuil, Yvonne I.; Trimbos, Krijn; Haddrath, Oliver; Baker, Allan J.; Piersma, Theunis (Molecular Ecology Resources, 2009)
We isolated and tested 16 microsatellite loci in black-tailed godwits from the Netherlands (Limosa limosa limosa), and from Australasia (subspecies melanuroides). One locus was monomorphic, two loci had null-alleles and one was significantly heterozygote deficient. The remaining 12 polymorphic loci had on average 7.9 alleles (range 5-11) and the mean expected heterozygosity was 0.69. No significant linkage disequilibrium between the loci was observed and all loci were autosomal. Fourteen loci were successfully cross-amplified in bar-tailed godwit (Limosa lapponica).